Risk factors for postoperative hypotension after adrenalectomy for phaeochromocytoma: derivation of the PACS risk score. Issue 2 (February 2023) - Parente, Alessandro; Thompson, Joseph P.; Crook, Charlotte; Bassett, Paul; Aspinall, Sebastian; Melvin, Ross; Stechman, Michael J.; Perry, Helen; Balasubramanian, Sabapathy P.; Pannu, Arslan; Palazzo, Fausto F.; Van Den Heede, Klaas; et al.
Abstract: Background: Due to the risk of postoperative hypotension (PH), invasive monitoring is recommended for patients who undergo adrenalectomy for phaeochromocytoma. Due to high costs and limited availability of intensive care, our aim was to identify patients at low risk of PH who may not require invasive monitoring. Methods: Data for patients who underwent adrenalectomy for phaeochromocytoma between 2012 and 2020 were retrospectively collected by nine UK centres, including patient demographics, intraoperative and postoperative haemodynamic parameters. Independent risk factors for PH were analysed and used to develop a clinical risk score. Results: PH developed in 118 of 430 (27.4%) patients. On univariable analysis, female sex (p = 0.007), tumour size (p < 0.001), preoperative catecholamine level (p < 0.001), open surgery (p < 0.001) and epidural analgesia (p = 0.006) were identified as risk factors for PH. On multivariable analysis, female sex (OR 1.85, CI95%, 1.09–3.13, p = 0.02), preoperative catecholamine level (OR: 3.11, CI95%, 1.74–5.55, p < 0.001), open surgery (OR: 3.31, CI95%, 1.57–6.97, p = 0.002) and preoperative mean arterial blood pressure (OR: 0.59, CI95%, 0.48–1.02, p = 0.08) were independently associated with PH, and were incorporated into a clinical risk score (AUROC 0.69, C-statistic 0.69). The risk of PH was 25% and 68% in low and high risk patients, respectively. Conclusion: The derived risk score allows stratification of patients at risk of postoperative hypotension after adrenalectomy for phaeochromocytoma. Postoperatively, low risk patients may be managed on a surgical ward, whilst high risk patients should undergo invasive monitoring.